World History, Volume II, 9th Edition - William Duiker (Cengage Learning, 2018)
Noted teachers and scholars William J. Duiker and Jackson J. Spielvogel present a balanced, compelling overview of world history that explores common challenges and experiences of the human past, and identifies key patterns over time. Political, economic, social, religious, intellectual, cultural, and military history -- presented in a chronological framework -- help students appreciate and understand the distinctive character and development of individual cultures in society. Themes (Science and Technology, Art and Ideas, Family and Society, Politics and Government, Earth and the Environment, Religion and Philosophy, and Interaction and Exchange), assist students in placing historical events and the contemporary world in a meaningful context. Available options: WORLD HISTORY, 9th Edition (Chapters 1-30); Volume I: To 1800 (Chapters 1-18); Volume II: Since 1500 (Chapters 14-30). Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.